Analisis Tarikan Berdasarkan Tata Guna Lahan di Kota Gorontalo (Studi Kasus: Jalan Prof. Dr. H.B Jassin Kota Gorontalo) - Ferrina Pangemanan Ano; Yuliyanti Kadir; Frice Lahmudin Desei (Transbahasa, 2025)
Transportation plays a crucial role in supporting daily human activities, with significant impacts on economic, social, and environmental aspects. In Gorontalo City, one of the main challenges is traffic congestion, particularly along Prof. DR. H.B. Jassin Street, which experiences high mobility due to diverse land use functions. This condition highlights the need to examine the extent to which land use influences travel attraction on this corridor. The aim of this study is to analyze the effect of land use variables—including building area, number of employees, and number of visitors—on travel attraction along Prof. DR. H.B. Jassin Street. The research employed field observations, surveys, and quantitative analysis using multiple linear regression with SPSS software. The results indicate that all three independent variables significantly affect travel attraction, with building area emerging as the most dominant factor in explaining variations in travel demand. Furthermore, the coefficient of determination shows that the regression model is capable of explaining most of the variations in travel attraction. These findings emphasize the importance of integrating land use considerations into urban transportation planning. Consequently, the study recommends the need for stricter land use management, improved transportation systems, and better road infrastructure arrangements to reduce traffic congestion while enhancing the quality of the urban environment in a more sustainable manner.